Behaviour of cold-formed high strength steel RHS under localised bearing forces. (15th March 2019) - Li, Hai-Ting; Young, Ben
Highlights: Bearing capacity of cold-formed high strength steel RHS was examined. A total of 37 web crippling tests was undertaken. Finite element models were developed and verified against the test results. Parametric study of 156 specimens was performed on both slender and stocky RHS. Existing web crippling provisions are evaluated and improved design rules are proposed. Abstract: The structural response of cold-formed high strength steel (CFHSS) rectangular hollow sections (RHS) under localised bearing forces is investigated. Web crippling tests were undertaken on cold-formed steel RHS that had nominal yield strengths (0.2% proof stresses) of 700 and 900 MPa. The experiments were conducted under end and interior load cases. The experimental results were utilised in a numerical investigation to verify finite element (FE) models. Upon verification, an extensive parametric study was conducted. The ultimate capacities obtained experimentally and numerically were compared with nominal resistances computed by the current North American Specification, European Code and Australian Standard. Overall, the codified resistance provisions gave either unconservative or overly conservative predictions. Therefore, improved design rules for CFHSS RHS under localised bearing forces were proposed. The reliability of the codified as well as modified design provisions were appraised. It is demonstrated that the modified design rules proposed in this paper can provide reliable predictions for the CFHSS RHS under localised bearing forces.